Qui sont les étudiantes du programme de formation francophone d’infirmières praticiennes? - Caty, Suzanne; Michel, Isabelle; Pong, Raymond; Stewart, Dianne (Ref;ets, 2007)

Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 4 - Identification of current bilingual human ressources and human resource practices - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
The first part of the comprehensive study entitled “Improving St. Boniface and St. Vital Seniors’ Access to French-language Health Services,” provided an overview of the health status and service needs of seniors in these two neighborhoods. The second part, focused on identifying available French-language health services, listed 106 public, community, private forprofit and private not-for-profit and community organizations offering Frenchlanguage services in St. Boniface and St. Vital. The goals of this fourth part of the study are to: 1) identify bilingual human resources able to serve seniors in French within these organizations across the continuum of care and 2) better understand current practices and challenges in recruiting, hiring and retaining professionals who can offer French-language services. Specifically, we will attempt to determine the number and percentage of professionals who can offer French-language services, identify the nature of services offered by these bilingual professionals, identify current practices for recruiting and hiring bilingual staff and identify the challenges in matching the needs of seniors with bilingual human resources. This will provide us with an overview of current bilingual human resources and human resource practices in designated bilingual or Francophone facilities, long-term care facilities and home care providers in St. Boniface and St. Vital.
Voir le rapport en anglais à partir de la page 36 du PDF joint.

Providers of language-appropriate health care providers are scarce: Self-declared language capabilities of the healthcare workforce in Ontario - Demers, Chantal; Bourgeault, Ivy Lynn; Leal, Andrew; Simkin, Sarah; Sweetman, Arthur

Equity, safety & health outcomes: The case for a national minimum data standard around health workforce language data in Canada - Demers, Chantale; Richard, Lise; Bourgeault, Ivy. Lynn

La formation à distance : un moyen novateur pour promouvoir la santé - Deroche, Francine; Simard, Anne (Reflets : Revue ontaroise d'intervention sociale et communautaire, 2007)
Cet article trace les grandes lignes d'un projet de formation à distance qui a été mis en oeuvre en Ontario français. Plusieurs leçons ont été tirées de cette expérience qui peuvent servir dans la planification de futures activités de formation.

Pas de problème: Rapport du comité d'action sur les services de santé en langue française, 1976 - Dubois, Jacques (Ministère de la santé, Ontario, 1976)
Ce rapport est le fruit des travaux du Comité d'action sur les services de santé en langue française, institué par le ministère de la Santé de l'Ontario et officialisé par un arrêté-en-conseil approuvé en février 1975. Le titre "Pas de problème" est choisi parce que selon le comité, il "résume assez bien la réponse des resposnables de services de santé qui n'ont pas encore perçu les besoins d'un groupe linguistique minoritaire. Pas de problème. Cette simplification d'une situation pourtant très complexe dénote sans doute l'attitude que rencontre trop souvent la population française de l'Ontario." Après une brève recension d'écrits (majoritairement américains) sur les barrières linguistiques en santé, le rapport fait un état des lieux en Ontario à cette époque et énonce plus d'une centaine de recommandations.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)
site internet de Research in focus: https://www.cranhr.ca/focus

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)
site internet de Focus sur la recherche: https://fr.cranhr.ca/focus

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)

Les Effets Potentiels de la Version Française du NCLEX-RN® sur le Choix de la Langue de Formation d'Étudiantes Infirmières Francophones en Situation Minoritaire. - Lalonde, Michelle; Chartrand, Julie; Vanderspank- Wright, Brandi; McGillis Hall, Linda; Gosselin-Bélanger, Amélie; Fullum, Jessica Adèle (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2020)
Background: Since the introduction of the new entry to practice exam, the NCLEX-RN®, there has been a very low success rate among Francophone nursing students living in minority situations. In addition, there has been a drop in the number of candidates who choose to write the exam in French. These results are of great concern in terms of the quality and sustainability of French language health services in French language minority communities in Canada. Objectives: The purpose of this article is to present the results of a study exploring the experiences of students enrolled in an entry level nursing program in French in terms of their decision-making regarding: 1) the choice of the language of the nursing program in which they were enrolled, 2) the language in which they chose to write the NCLEX-RN®, 3) their interest in working in a Francophone context, 4) their general knowledge of the new entry to practice exam, and 5) information sources on the NCLEX-RN©. Methodology: A sequential mixed methods design using surveys with multiple-choice and open-ended questions was used to conduct this study. Descriptive analyzes, as well thematic and content analysis, were used to analyze the data. Results: 51 students from a francophone graduating cohort participated in this study. The majority of the participants expected to write the NCLEX-RN® in English; the media attention on the French version of the exam influenced their decision. Four main themes were highlighted : 1) Choice of language of student based on their first language, 2) Three main factors that influence the choice of the language in which they write the NCLEX-RN®, 3) Colleagues and media as sources of information on the NCLEX-RN®, and 4) Importance and pride of studying in French. Conclusion: The results of this project shed light on the factors that influence francophone students' decision-making regarding the choice of language for the exam and the reasons why graduating students would choose to study in French again or not. , Contexte : Un très faible taux de réussite a été remarqué chez les étudiantes infirmières francophones en situation minoritaire ainsi qu’une chute du nombre de candidates qui choisissent de passer en français le nouvel examen d’autorisation, le NCLEX-RN®, qui a été introduit en 2015. Ces données sont préoccupantes s’agissant de la qualité et de la pérennité des services de santé en français dans les régions linguistiques minoritaires au Canada. Objectifs : Le but de cet article est de présenter les résultats concernant les expériences des étudiantes inscrites dans un programme de formation initiale en sciences infirmières en français sur leur prise de décision quant à : 1) la langue du programme auquel elles se sont inscrites, 2) la langue dans laquelle elles ont choisi de passer le NCLEX-RN®, 3) leur intérêt à travailler dans un contexte francophone, 4) leurs connaissances générales relatives au nouvel examen d’autorisation et 5) les sources d’information sur le NCLEX-RN®. Méthodologie : Un devis de recherche mixte séquentiel a été retenu comportant l’utilisation de questionnaires. Des analyses descriptives et des analyses thématiques et de contenu ont été effectuées. Résultats : 51 étudiantes de la cohorte francophone ont participé à cette étude. La majorité des participantes comptaient passer le NCLEX-RN® en anglais; l’intérêt médiatique porté à la version française de l’examen a eu une influence sur leur décision. Quatre grands thèmes ont été mis en évidence à partir des questions à court développement du questionnaire : 1) langue maternelle choisie comme langue de formation, 2) trois principaux facteurs qui influencent le choix de la langue pour le NCLEX-RN®, 3) collègues et médias comme sources d’information sur le NCLEX-RN®, et 4) importance et fierté d'étudier en français. Conclusion : Les résultats de ce projet ont mis en évidence les facteurs qui influencent la prise de décision des étudiants francophones quant au choix de la langue de l’examen et les raisons pour lesquelles les finissantes étudieraient à nouveau en français.

Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Report on the 2020–2023 Café de Paris Manitoba Pilot Project - Roberge, Jérémie (Santé en français Manitoba, 2023)

Recruiting service providers with French proficiency: Tips and strategies - Schutte, Valerie; Erbach, Madison; Summers, Nikky; Jennings, Melissa (The Knowledge Institute on Child and Youth Mental Health and Addictions, 2023)

L’offre active des services de santé et de mieux‑être en français au Nouveau‑Brunswick - Société Santé en français et les Réseaux de santé en français

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.